PENGEMBANGAN ANIMASI 3D VENTILATOR PADA STEQHOQ ROBOTIKA INDONESIA - Halim D, R.M. Nasrul; Putra, Deka Widi (POLITEKNIK NEGERI JAKARTA, 2023)
Abstract - PT. Stechoq Robotika Indonesia is a company engaged in the field of intelligent systems and manufacturing engineering for both software and hardware. Along with the development of technology and the increasing need for technology-based systems, Stechoq focuses on product development with information systems in the form of multimedia. Because Covid-19 patients with severe PDP status (patients under surveillance) usually cannot breathe normally, a ventilator is needed to breathe. As a result of the large number of patients, a ventilator is also needed, while the number of these devices is still very limited due to the limitations of the device, it is being developed. it is necessary to make this 3D animation video to educate the public to be more careful about the dangers of the Covid-19 virus. Animation is created using the MDLC multimedia development life cycle method. The MDLC method has six stages, namely, concept, design, material collecting, assembly, testing, and distribution. These six stages can help during the process of making a 3d ventilator animation development video. The results of this study are a 3D Ventilator animation which is expected to educate the public about the dangers of viruses and if there is a shortage of ventilators.